Pleasure - Avery, John (Forced Entertainment, 1998)
If each of Forced Entertainment's pieces were a room in a house 'Pleasure' would definitely be the basement - a dark, scary place where the stage-hands are snogging and where the acts are more dangerous than they seem. Created in 1997 'Pleasure' toured throughout the UK and mainland Europe. In July 1997 it was the subject of a South Bank Show documentary film 'On Pleasure' by Alexander Kelly in collaboration with the company
High quality multi-camera performance documentation